Individual and Group Aspects in Influencing Organizational Performance - Abdillah, Said Ridho; Yusriani, Sri; Patiro, Shine Pintor Siolemba; Rekarti, Endi; Amalia, Alona (Jurnal Bisnis Mahasiswa, 2024)
This research explores the individual and group aspects influencing organizational performance. The individual aspects examined include motivation, leadership, and commitment, while the group aspects include group dynamics, collaboration, and trust. This study uses a literature review methodology, analyzing various journals and published books. Relevant theories are discussed to provide a comprehensive understanding of the topic. The findings suggest that both individual and group aspects significantly affect organizational performance, each contributing to improving organizational effectiveness. This research highlights the interconnectedness of individual and group factors in enhancing overall organizational success.